Plan para la dirección del proyecto ampliación de la oferta de servicios de consulta médica homeopática en el Área de Salud de Curridabat - Solís-Agüero, Sedalí (Instituto Tecnológico de Costa Rica, 2013)
The objective of the research is to provide the Project Management Plan of the project “Medical Services Offering Extension of the Homeopathic Consultation” to Curridabat Health Area, belonging to the Integral Health Program of the University of Costa Rica. Due to the nature, novelty, uncertainty and diversity of stakeholders, it is considered that professional planning can ensure greater likelihood of success. There is a previous experience of homeopathic medical consultation in this country, and the interest from the Social Security Fund to incorporate that service in social security. Internationally Homeopathy is part of the systems and public health insurance, particularly in developed countries. The Project Management Plan is considered one of the critical success factors, such as environmental factors, and organizational capabilities in project management. The challenge in managing projects in health services is to adapt the best practices of the PMBOK Guide, to the particularities of such projects, where stakeholder management, communication, quality and risk management are vital. To achieve the objectives of the project it were used main document review techniques, mostly from primary sources and field research primarily through interviews. It offers professional planning for the implementation of a homeopathic consultation in the area of health of Curridabat, through the development of tools and techniques that allowed to consolidate sub-plans from most of the areas of knowledge that are proposed in the Guide PMBOK ®.
Proyecto de Graduación (Maestría en Gerencia de Proyectos con Énfasis en Proyectos Empresariales) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2013.
Keywords: Administración de proyectos; Planificación; Salud; Atención médica; Seguro social